2021
DOI: 10.1186/s12887-021-02678-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of bullying perpetration among Lebanese adolescents: a national study

Abstract: Background Presently, 1 in 4 Lebanese adolescents is involved in bullying, with 12% being perpetrators. In Lebanon, around 90% of bullying incidents occur in schools. Given the lack of studies tackling bullying perpetration in Lebanon, this study aims to identify and target risk factors of bullying perpetration among Lebanese adolescents, which would serve future prevention and intervention programs. Methods This cross-sectional study took place be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Third, given the previous indirect evidence between these three variables ( 76 , 79 ), we further examined the mediating role of IGD. As expected, hypothesis 3 was also validated that IGD mediates the relationship between school assets and bullying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, given the previous indirect evidence between these three variables ( 76 , 79 ), we further examined the mediating role of IGD. As expected, hypothesis 3 was also validated that IGD mediates the relationship between school assets and bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Karatoprak et al ( 78 ) noted that internet addiction was predictive of both bullying and victimization. An investigation also revealed the predictive effect of internet addiction on bullying ( 79 ). Likewise, Kim et al ( 80 ) found that online game addiction was a risk factor for school violence perpetration.…”
Section: Introductionmentioning
confidence: 99%
“…They had the right to accept or refuse to enroll in the study; those who agreed to participate received no financial rewards in return. The methodology used in this study is the same as the one used in previous papers [ 27 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Excluded were students that declined to fill the survey. This paper shares the same methodology as other papers from the same project [22][23][24][25][26][27].…”
Section: Participants and Proceduresmentioning
confidence: 99%